Money Dysmorphia Dan Subjective Financial Well-Being Mahasiswa UIN Palangka Raya: Hubungan Persepsi Dan Realitas Finansial - Zamzam Badrouzzaman; Yoga Tri Cahyono; Iqbal Nur Hilmi; Muhammad Hasan; Surawan Surawan (Nathiqiyyah, 2026)
Changes in economic dynamics and increasing social exposure in the digital era influence how students perceive their financial conditions and may lead to the phenomenon of money dysmorphia, a distortion in evaluating financial reality. This study aims to analyze the relationship between money dysmorphia and subjective financial well-being among students of the Islamic Education Program at UIN Palangka Raya. This research employed a mixed methods approach with a sequential explanatory design. Quantitative data were collected through a Likert-scale questionnaire distributed to 22 students, and analyzed using descriptive statistics and correlation analysis. The qualitative stage was conducted to explore students’ experiences and provide deeper explanations of the quantitative findings. The results show that the average score of money dysmorphia reached 41.76%, which falls into the low category based on the percentage of the maximum questionnaire score. A similar average score (41.76%) was found for subjective financial well-being, also categorized as low. The findings indicate a negative relationship between money dysmorphia and subjective financial well-being, where higher distortion in financial perception is associated with lower perceived financial well-being. These results suggest that students’ financial well-being is influenced not only by objective economic conditions but also by psychological factors such as financial perception and social comparison.